Carbon fabric supported 3D cobalt oxides/hydroxide nanosheet network as cathode for flexible all-solid-state asymmetric supercapacitor. Issue 33 (3rd August 2018) - Qin, Tianfeng; Dang, Shan; Hao, Jiaxin; Wang, Zilei; Li, Haoqian; Wen, Yuxiang; Lu, Shuqi; He, Deyan; Cao, Guozhong; Peng, Shanglong
Abstract : 3D interconnected Co oxides/hydroxide nanosheets array with high specific surface area and small crystalline size is fabricated and shows excellent rate ability. Abstract : Owing to a lack of electroactive sites and poor conductivity, Co oxides/hydroxides nanosheet network electrodes usually show low experimental capacity, hardly meeting the demand for high energy density needed for an asymmetric supercapacitor. Herein, we demonstrate a surface capacity enhancement of a 3D cobalt oxides/hydroxides nanosheet network cathode through a simple cyclic voltammetry electro-deposition method. By optimizing the electro-deposition parameters, the as-prepared Co oxides/hydroxides nanosheet network electrode delivers a significantly high capacity of 427 C g −1 at the current density of 1 A g −1 and excellent rate ability of 79.8% at the current density of 10 A g −1, as well as outstanding cycling life. A detailed voltammetric analysis using the power-law relationship and Trasatti's method shows that both the large surface area, high pore volume and polycrystalline nature contribute to the enhancement of the surface capacity. In addition, the assembled asymmetric all-solid-state supercapacitor also presents a volume energy density of 2.78 mW h cm −3 at a power density of 14 mW cm −3 and excellent cycling stability. In addition, our prepared asymmetric supercapacitor shows super flexibility and was used to light up a heart-shaped logo. This work may provide valuable insights into the design and fabrication of electrode materials with improved capacity and rate ability.